The future of impact metric use among collection development librarians - Sutton, Sarah; Miles, Rachel; Konkiel, Stacy (Qualitative and Quantitative Methods in Libraries, 2019)
Collection development librarians often use metrics such as usage statistics, citation counts, and journal impact factors to inform their collection management decisions. How might newer metrics like altmetrics (data sourced from the social web that exposes how research is discussed, shared, bookmarked, and reused) complement those already in use? In this paper, the authors discuss the results of a nationwide survey of US academic librarians working at R1 institutions that sought to understand the extent to which librarians use altmetrics in the course of their daily work. In particular, we examine collection development librarians’ awareness of altmetrics and other impact metrics; how often collection development librarians are using altmetrics to make decisions regarding their collections; and whether the disciplines with which collection development librarians liaise have an effect on librarians’ awareness of altmetrics. The survey results are then discussed in the context of the challenges and opportunities that exist for the use of altmetrics in the future of library collection development practices